TELAAH ARTIKEL ILMIAH EFEKTIFITAS KOMPRE DINGIN TERHADAP PENURUNAN INTENSITAS NYERI LUKA PERINEUM IBU POST PARTUM - Ayu Agustina; Agustina Ningsi; Marhaeni Marhaeni; Sitti Mukarramah (Madu : Jurnal Kesehatan, 2020)
Every mother who has undergone a labor process with a perineal wound will feel pain, pain that is felt by every post partum mother causes discomfort so that pain management is needed. The purpose of this journal study was to determine the effectiveness of cold compresses in reducing the intensity of perineal wound pain in post partum mothers. The literature search method was the Google Scholar database using the keywords cold compress, perineal wound pain. The study population in the article studied were post partum mothers who experienced perineal wound pain with the research sample in article one of 30 people, 15 people in article two, and 200 people in article three. Articles one and two used the one group pretest post test research design, while the pepper article three used the control group pretest post test. The article review process includes a review of the components of the article regarding the systematics of writing, language style, advantages and disadvantages. The results of the review of the article show that cold compresses are effective in reducing the intensity of post partum maternal perineal wound pain. This journal review is expected to be a reference in the implementation of perineal wound pain management in post partum mothers.